DISTRIBUTION OF WATER POLLUTION AREAS BASED ON THE KERNEL DENSITY METHOD FOR LAPINDO MUDFLOW DISASTER OF SIDOARJO - Shofwan, Moch; Aini, Farida Nur (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2020)
The Lapindo mudflow disaster in Sidoarjo Regency which occurred on May 29, 2006 is a natural event that is classified as high risk. This disaster has a significant impact, especially for the water pollution caused by various conditions due to the Lapindo mudflow disaster. The purpose of the study is to mapping the location and analyze the distribution of water pollution based on the kernel density method. This research uses spatial approachment through descriptive-quantitative, qualitative and explorative methods. Primary and secondary data are both used in the research. The research results showed that water pollution is found on the north, west, south and east sides of the Lapindo mudflow disaster area in villages in three sub-districts namely Porong, Tanggulangin, and Jabon with the highest radius of pollution risk maximum of 1 Km from the center of the mudflow. The results of the distribution of water pollution areas based on the method of kernel density showed that the distribution of the highest water pollution leads to the north and west sides of the center of the mudflow.